I've Got a Testimony: James Baldwin and the Broken Silences of Black Queer Men. (13th December 2016) - Melton, McKinley E
Abstract : James Baldwin writes within and against the testimonial tradition emerging from the Black Church, challenging the institution's refusal to acknowledge the voices and experiences of black queer men. Baldwin's autobiographical novel, Go Tell It on the Mountain, creates a space for Baldwin's testimony to be expressed, and also lays the foundation for a tradition of black queer artists to follow. In the contemporary moment, poet Danez Smith inhabits Baldwin's legacy, offering continuing critiques of the rigidity of conservative Christian ideologies, while publishing and performing poetry that gives voice to their own experiences, and those of the black queer community at large. These testimonies ultimately function as a means of rhetorical resistance, which not only articulates black queer lives and identities, but affirms them.